Regularized MFS solution of inverse boundary value problems in three-dimensional steady-state linear thermoelasticity. (August 2016) - Marin, Liviu; Karageorghis, Andreas; Lesnic, Daniel
Abstract: We investigate the numerical reconstruction of the missing thermal and mechanical boundary conditions on an inaccessible part of the boundary in the case of three-dimensional linear isotropic thermoelastic materials from the knowledge of over-prescribed noisy data on the remaining accessible boundary. We employ the method of fundamental solutions (MFS) and several singular value decomposition (SVD)-based regularization methods, e.g. the Tikhonov regularization method (Tikhonov and Arsenin, 1986), the damped SVD and the truncated SVD (Hansen, 1998), whilst the regularization parameter is selected according to the discrepancy principle  (Morozov, 1966), generalized cross-validation criterion (Golub et al., 1979) and Hansen's L-curve method (Hansen and O'Leary, 1993).